(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
The key issue that emerges from the reports of Martínez-Torrón can be summarised in one question: “can religious freedom be guaranteed in exceptional circumstances?”. The immediate answer is just: “yes, it can”. Clearly, we must be able to find proper ways to do that, while bearing in mind that it is not only a question of verifying whether it is possible to do so, because protecting religious freedom is not just an option among many others, but it is an unavoidable necessity.